ANALISIS ASPEK LINGUAL MANTRA KESELAMETAN PANOLAK SANGKIL (Kajian Etnolinguistik) - Alwiyah, Sayyidah Achmadah (University of Brawijaya, 2022)
ABSTRACT: This study examines the mantra used by the people of Dukuan Hamlet, Metatu Village, Benjeng District, Gresik Regency when doing a safar (trip). The Panolak Sangkil Safety Mantra is used by the surrounding community to fortify themselves from disturbance by supernatural beings, evil spirits and spirits during the trip. This study uses an ethnolinguistic approach and interviews and documentation. The research data is provided by the method of observing, recording, and recording and presenting the data with data reduction, translation, validation, analysis, and interpretation. The results of research on the lingual aspect of the mantra found (1) repetition consisting of grammatical, lexical and semantic repetition patterns, (2) semantic decomposition, (3) saroja words, (4) metaphors, (5) mention of mythological figures, and ( 6) mention of god. From the analysis, it is found that the language aspect of the mantra is related to the culture of the Gresik people.